2015
DOI: 10.1007/s10519-015-9740-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recent Stress and Variation in the Serotonin Transporter Polymorphism (5-HTTLPR) on Depressive Symptoms: A Repeated-Measures Study of Adults Age 50 and Older

Abstract: Depending on genetic sensitivity to it, stress may affect depressive symptomatology differentially. Applying the stress-diathesis hypothesis to older adults, we postulate: (1) recent stress will associate with increased depressive symptoms levels and (2) this effect will be greater for individuals with at least one short allele of the serotonin transporter gene promoter region (5-HTTLPR). Further, we employ a design that addresses specific limitations of many prior studies that have examined the 5-HTTLPR x SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…This polymorphism was initially shown to interact with the number of SLEs occurring over the last year to predict LLD in Korean elders, with S allele carriers exhibiting higher LLD risk when exposed to greater numbers of SLEs [ 49 ]. Nonetheless, subsequent reports examining LLD symptomatology in other ethnicities found no significant interactions between 5-HTTLPR and SLEs occurring within the last one or two years [ 50 - 52 ]. When examining the longitudinal course of LLD, the 5-HTTLPR polymorphism was shown to moderate the impact of SLEs occurring within the last year, with S allele carriers demonstrating higher probability to remit when having higher baseline number of SLEs and greater SLE reduction over time [ 28 ].…”
Section: Gene-stress Interactions and Late-life Neuropsychiatric Syndmentioning
confidence: 99%
“…This polymorphism was initially shown to interact with the number of SLEs occurring over the last year to predict LLD in Korean elders, with S allele carriers exhibiting higher LLD risk when exposed to greater numbers of SLEs [ 49 ]. Nonetheless, subsequent reports examining LLD symptomatology in other ethnicities found no significant interactions between 5-HTTLPR and SLEs occurring within the last one or two years [ 50 - 52 ]. When examining the longitudinal course of LLD, the 5-HTTLPR polymorphism was shown to moderate the impact of SLEs occurring within the last year, with S allele carriers demonstrating higher probability to remit when having higher baseline number of SLEs and greater SLE reduction over time [ 28 ].…”
Section: Gene-stress Interactions and Late-life Neuropsychiatric Syndmentioning
confidence: 99%
“…Allele variants of 5‐HTTLPR (central serotonin 5‐HT transporter promoter region) seem to be accountable for the effective concentration and activity of serotonin, which means these variants control the prompt ejaculation. Usually, three types of allele variants are reported: LL, SL/LS, and SS having insertion and deletion of the 44‐bp fragment in long (L) and short (S) alleles, respectively (Arpawong et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…10 Previous research from our group demonstrated that presence of the s-allele was associated with higher waking cortisol and lower delayed recall in older adults, with reduced hippocampal volume among s-allele carriers with higher waking cortisol. 11 Meta-analyses have further revealed that s-allele status is associated with increased stress sensitivity 12,13 and increased cortisol reactivity. 11,14 Most recently, Smith et al 15 found late-life serotonin depletion in individuals with mild neurocognitive impairment (MCI).…”
Section: Introductionmentioning
confidence: 99%